Analysis and design of a high power density permanent magnet-assisted synchronous reluctance machine with low-cost ferrite magnets for EVs/HEVs. Issue 6 (7th November 2016) - Liu, Xiping; Li, Ya; Liu, Zhangqi; Ling, Tao; Luo, Zhenhua
Abstract : Purpose: The purpose of this paper is to propose a permanent magnet-assisted synchronous reluctance machine (PMASynRM) using ferrite magnets with the same power density as rare-earth PM synchronous motors used in Toyota Prius 2010. Design/methodology/approach: A novel rotor structure with rectangular PMs is discussed with respect to the demagnetization of ferrite magnets and mechanical strength. Some electromagnetic characteristics including torque, output power, loss and efficiency are calculated by 2D finite element analysis. Findings: The results of the analysis show that a high power density and high efficiency for PMASynRM can be achieved using ferrite magnets. Originality/value: This paper proposes a novel rotor structure of PMASynRM with low-cost ferrite magnets that achieves high power density as permanent machines with rare-earth PMs.